Intestinal Parasitic Infestation: Analysis Over One Year at Shree Birendra Hospital, Chhauni - Pandey, J S; Panta, R (Medical Journal of Shree Birendra Hospital, 2005)
Intestinal Parasitic Infestation: Analysis Over One Year at Shree Birendra Hospital, Chhauni